KEKERASAN SIMBOLIK (SYMBOLIC VIOLENCE) TERHADAP SUKU JAWA DALAM PROGRAM TV “ HIDUP INI INDAH“ DI TRANS TV - Hasfi, Nurul (FORUM, 2011)
Abstract :Symbolic violence of ethnic in television program still get low attention from Indonesian media content controller (KPI, LSF) as well as audiences because it is done implicitly and unconsciously. On the other hand, the impact is as dangerous as physical violence in television program such us killing, shooting, hitting. This paper try to evaluate content of a television program, 'Hidup Ini Indah', produced by Trans TV that is indicated do symbolic violence to 'Javanese'. Symbolic violence hazard integration of a multicultural society in Indonesia as it produce discrimination of 'dominant culture' over 'minority culture'. By using the basis of Representation Theory (Stuart Hall: 1979) this paper try describe and explain how language (text, symbol, visual, object, event) has produced certain meaning, called 'stereotype' that is identified as symbolic violence. Key words: symbolic violence, stereotype, representation, dominant culture, minority culturepermalink: http://ejournal.undip.ac.id/index.php/forum/article/view/3157